2019
DOI: 10.1111/cas.13995
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter 1 regulates the proliferation and cisplatin sensitivity of esophageal cancer

Abstract: Glucose transporter 1 ( GLUT 1) expression is a prognostic marker for esophageal squamous cell carcinoma ( ESCC ). Recent work on GLUT 1 and development of specific inhibitors supports the feasibility of GLUT 1 inhibition as a treatment for various cancers. The anti–proliferative effects of GLUT 1‐specific small interfering RNA (si RNA ) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…WZB117 has also been successfully applied together with 5‐fluorouracil on resistant colon carcinomas (HCT116), which can be most probably explained with an observed GLUT‐1 upregulation in 5‐fluorouracil‐resistant and ‐treated colon cells . The GLUT‐1‐selective inhibitor BAY‐876 enhanced the response of cisplatin‐treated esophageal squamous cell carcinoma with respect to cell proliferation . Radiation of a tumor acts through creating double‐strand breaks in DNA as well as through cellular water radiolysis, which creates ROS .…”
Section: Combination Studiesmentioning
confidence: 97%
See 3 more Smart Citations
“…WZB117 has also been successfully applied together with 5‐fluorouracil on resistant colon carcinomas (HCT116), which can be most probably explained with an observed GLUT‐1 upregulation in 5‐fluorouracil‐resistant and ‐treated colon cells . The GLUT‐1‐selective inhibitor BAY‐876 enhanced the response of cisplatin‐treated esophageal squamous cell carcinoma with respect to cell proliferation . Radiation of a tumor acts through creating double‐strand breaks in DNA as well as through cellular water radiolysis, which creates ROS .…”
Section: Combination Studiesmentioning
confidence: 97%
“…However, care should be taken when selecting an appropriate cell line. BAY‐876 has been successfully applied to esophageal squamous cancer cell lines TE‐8 and TE‐11 in combination with cisplatin …”
Section: Discovery Of the Most Potent Glut Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have revealed that enhanced glycolysis is associated with aggressiveness and poor prognosis in multiple cancers [16][17][18]. Accumulating data have also indicated that elevated aerobic glycolysis in cancer cells is critical for chemoresistance [18][19][20]. Taken together, the diverse roles of aerobic glycolysis in cancer suggest that alterations in the glycolytic pathway may influence chemotherapy outcomes.…”
Section: Introductionmentioning
confidence: 99%